Coordination chemistry of Zn2+ with Sal(ph)en ligands: Tetrahedral coordination or penta‐coordination? a DFT analysis. Issue 5 (14th December 2018) - Lamine, Walid; Boughdiri, Salima; Christ, Lorraine; Morell, Christophe; Chermette, Henry
Abstract : In this article, the Lewis acidic character within a series of Zn‐Sal(ph)en complexes is reviewed and revisited. Besides traditional analyses found in the literature, conceptual density functional theory descriptors are used to assess this acidic character. Using these tools, we highlight how the nature of the bridging diamine linker in the Schiff base ligand controls this feature mainly responsible of the coordination geometry of these complexes. This Lewis acidic behavior is addressed first by application of the usual dual descriptor to a prototypical complex, namely ZnCl4 2− . However, the usual dual descriptor exhibits significant weaknesses to retrieve the electrophilic part on the metal cation of Zn‐sal(ph)en complexes. The inclusion of the densities of the electronic excited states through the so‐called state‐specific dual descriptor allows us to recover successfully the appropriate reactivity of these chosen complexes with different diamine bridges in flexible to semirigid, and then to rigid ranges. The coordination of the Zn 2+ is shown to be dictated by the geometry of the sal(ph)en ligand. © 2018 Wiley Periodicals, Inc. Abstract : Intrinsic connection between the Lewis acidic character and the specific shape of 1, 2‐diimine bridge within Zn‐sal(ph)en complexes is studied to understand their coordination chemistry and reactivity. For this purpose, nucleophilic and electrophilic sites are discriminated thanks to conceptual density functional theory descriptors. In a first stage, a prototype complex, namely [ZnCl4 ] 2−, is examined, and the results have been generalized to Zn‐sal(ph)en complexes with different diamine bridges through flexible, semirigid, and rigid ranges.